Effect of Essential Oils of Syzygium aromaticum and Melaleuca alternifolia on Isolates of Aspergillus sp. - A. Lima (Scientific Electronic Archives, 2014)
Essential  oils  have  antimicrobial  substances,  lower  cost  and  the  lower  resistance  of microorganism. This study aimed to evaluate the inhibition of mycelial growth of Aspergillus flavus and  A.  niger  with  essential  oils  of  Syzygium  aromaticum  and  Melaleuca  alternifolia.  For  this, aliquots  (0.5,  5,  10  and  15μL)  of  essential  oils  from  S.  aromaticum  and  M.  alternifolia   were distributed on the surface of the culture medium Potato Dextrose Agar (PDA) with Drigaslsky. In the control treatment were used only plates containing PDA plus chloramphenicol (1%). After 2 hours, a disc (8mm diameter) of the isolated mycelium, with 10 days of age on PDA, was peaked to the center of the plates, these plates were sealed and incubated at 282°C, in the dark. The essential  oil  of  S.  aromaticum  inhibited  the  mycelial  growth  of  A.  flavus  and  A.  niger,  in  all aliquots. When using the essential oil of M. alternifolia decreased the mycelial growth of A. flavus in all aliquots, however, showed a low efficiency in control of A. niger. It was concluded that the essential  oil  S.  aromaticum  is  effective  against  A.  flavus  and  A.  niger,  which  can  be  used  in control against these microorganisms, and M. alternifolia not show satisfactory results in relation to reducing the growth of pathogens evaluated.